The world, the flesh and the subject : continental themes in philosophy of mind and body - Gilbert, Paul, 1942- (Edinburgh University Press, 2005)
Here, for the first time, contemporary Continental thought comes into conversation with analytic philosophy on all the principal topics of philosophy of mind. Rejecting the dominant Anglo-American paradigm, which reduces mental phenomena to their roles in a scientific psychology, the authors present a non-mysterious, naturalistic alternative. Characterising mental life is, they seek to show, capturing the world from the point of view of the subject. But the subject is essentially embodied, so that mental phenomena are modes of our fleshly existence in the world. The book aims to bring together these three themes - the world,the flesh and the subject - to resolve many of the puzzles that beset contemporary philosophy of mind. It thereby provides a coherent new approach which draws upon phenomenology, hermeneutics, psycho-analysis and poststructuralism, and relates recent feminist work on the body to traditional concerns with the mind. The topics discussed include the problem of consciousness, perception and sensation, imagination, desire, emotion, reason and agency, and the self and others. Key Features Brings continental thought to bear on contemporary philosophy of mind Offers a new approach to problems of mind Brings recent work on the body together with traditional concerns with the mind Treats philosophy of mind in a topic oriented way